2020
DOI: 10.1002/pmic.202000246
|View full text |Cite
|
Sign up to set email alerts
|

N‐Terminomics for the Identification of In Vitro Substrates and Cleavage Site Specificity of the SARS‐CoV‐2 Main Protease

Abstract: The genome of coronaviruses, including SARS‐CoV‐2, encodes for two proteases, a papain like (PLpro) protease and the so‐called main protease (Mpro), a chymotrypsin‐like cysteine protease, also named 3CLpro or non‐structural protein 5 (nsp5). Mpro is activated by autoproteolysis and is the main protease responsible for cutting the viral polyprotein into functional units. Aside from this, it is described that Mpro proteases are also capable of processing host proteins, including those involved in the host innate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
116
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(131 citation statements)
references
References 18 publications
9
116
0
Order By: Relevance
“…The GTRVQ*SVEQI sequence motif is fully identical in the highly homologous CTBP1 and CTBP2 human proteins ( Figure S2 ), therefore, CTBP2 is likely to be a target of SARS-CoV-2 3CL protease as well. In agreement with this, CTBP2 has been proved to be a proteolytic target of hCoV-NL63 3CLpro [ 21 ], and the highly similar cleavage site specificities imply that CTBP proteins may be potential targets of SARS-CoV and SARS-CoV-2 3CLpro enzymes, but their susceptibility for proteolytic cleavage needs to be investigated in the context of other cell types and/or species, as well.…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…The GTRVQ*SVEQI sequence motif is fully identical in the highly homologous CTBP1 and CTBP2 human proteins ( Figure S2 ), therefore, CTBP2 is likely to be a target of SARS-CoV-2 3CL protease as well. In agreement with this, CTBP2 has been proved to be a proteolytic target of hCoV-NL63 3CLpro [ 21 ], and the highly similar cleavage site specificities imply that CTBP proteins may be potential targets of SARS-CoV and SARS-CoV-2 3CLpro enzymes, but their susceptibility for proteolytic cleavage needs to be investigated in the context of other cell types and/or species, as well.…”
Section: Resultsmentioning
confidence: 78%
“…First, we compared the autoproteolytic cleavage site sequences of SARS-CoV and SARS-CoV-2 3CLpro and found that the recognition sites closely resemble each other ( Figure 2 ). Similar to SARS-CoV [ 21 , 30 ], SARS-CoV-2 3CLpro cleavage sites also contain a conserved Gln residue in the P1 position, and there are hydrophobic (Leu, Phe, or Val) and small aliphatic residues (mainly Ser or Ala) in P2 and P1’ positions, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations